1990
DOI: 10.1143/jjap.29.l952
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ag-Sheathed (Tl, Bi)-Ca-Sr-Cu-O Superconducting Wire

Abstract: In the Tl-Bi-Ca-Sr-Cu-O system, Tl-O single layered superconducting phases of (Tl, Bi)CaSr2Cu2O x and (Tl, Bi)Ca2Sr2Cu3O x have been obtained. We prepared Ag-sheathed wire using the oxide powder of the (Tl, Bi)Ca2Sr2Cu3O x phase with T c of 113 K. With a decrease in the thickness of the rectangular wire specimen, J c at 77 K increases rapidly, reaching a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…For purposes of comparison, all tapes were rolled under the same conditions. Investigators have found that J c values of PIT tapes are inversely proportional to tape thickness until core uniformity is degraded at very small thickness [18], and that J c increases by one order of magnitude when tape thickness is reduced to 50 µm [19]. The tapes in the present study were rolled to a final thickness of 300 µm, below which core uniformity was lost.…”
Section: Resultsmentioning
confidence: 71%
“…For purposes of comparison, all tapes were rolled under the same conditions. Investigators have found that J c values of PIT tapes are inversely proportional to tape thickness until core uniformity is degraded at very small thickness [18], and that J c increases by one order of magnitude when tape thickness is reduced to 50 µm [19]. The tapes in the present study were rolled to a final thickness of 300 µm, below which core uniformity was lost.…”
Section: Resultsmentioning
confidence: 71%
“…Because of the higher irreversibility line of the Tl-1223 system when compared to that of Tl-2223, a significant effort has been devoted mainly to the development of Tl-1223 tape wire [11,12,24,25,[36][37][38][39][40][41][42][43][44][45][46]81]. In order to stabilize the 1223 phase and to optimize the weak links and pinning properties of the two basic Tl-Ba-Ca-Cu-O and Tl-Sr-Ca-Cu-O compounds [12,24,35,36], various types of structural substitutions have been gradually applied [11,25,[37][38][39][40][41][42][43][44]81] from which the best known are those with Tl-sites partially replaced by Pb or Bi, or by both, and the Sr-sites partially or entirely substituted by Ba. In one case, the partial replacement of Tl by V and Sr by Ba has been reported [39].…”
Section: Single-layer System Tl-1223 Tapesmentioning
confidence: 99%
“…However, a small change in the Sr/Ba of 1.6/0.4 caused a dramatic decrease in J c even without any external magnetic fields. Using also the results of other authors, [41] (table 1, number 1) instead of a partial substitution of Tl by Pb, they partially substituted Tl with Bi to prepare (Tl 0.78 Bi 0.22 )(Sr 0.8 Ba 0.2 ) 2 Ca 2 Cu 3 O x / Ag tape samples (table 1, number 5). In order to investigate a possible improvement of both the alignment and closer contact of grains, a uniaxial compression of rolled final tapes was applied and its effect upon the eventual J c improvement studied (the dr-ro-si and pr-si method) [44].…”
Section: Single-layer System Tl-1223 Tapesmentioning
confidence: 99%